A Review of H2, CH4, and Hydrocarbon Formation in Experimental Serpentinization Using Network Analysis - Barbier, Samuel; Huang, Fang; Andreani, Muriel; Tao, Renbiao; Hao, Jihua; Eleish, Ahmed; Prabhu, Anirudh; Minhas, Osama; Fontaine, Kathleen; Fox, Peter; Daniel, Isabelle (Frontiers in Earth Science, 2020)
The origin of methane and light hydrocarbons (HC) in natural fluids from serpentinization has commonly been attributed to the abiotic reduction of oxidized carbon by H2 through Fischer-Tropsch Type (FTT) reactions. Multiple experimental serpentinization studies attempted to identify the parameters that control the abiotic production of H2, CH4, and light HC. H2 is systematically and significantly formed in experiments, indicating that its production during serpentinization is well established. However, the large variance in concentration (eight orders of magnitude) is difficult to address because of the large number of parameters that vary from one experiment to another. CH4 and light HC production is much lower and also highly variable, leading to a vivid debate on potential role of metal catalysts and organic contamination. We have built a dataset that includes experimental setups, conditions, reactants, and products from 30 peer-reviewed articles reporting on experimental serpentinization and performed dimensionality reduction and network analysis to achieve an unbiased reading of the literature and fuel the debate. Our analysis distinguishes four experimental communities that highlights usual experimental protocols and the conditions tested so far. As expected, H2 production is mainly controlled by T and P though a strong variability remains within a given P-T range. Accessory metal-bearing phases seem to favor H2 production, while their role as catalyst or reactant is hampered by the lack of mineralogical characterization. CH4 and light HC concentrations are highly variable, uncorrelated to each other, and much lower than concentrations of potential reactants (H2, initial carbon). Accessory phases proposed as FTT catalysts do not enhance CH4 production, confirming the inefficiency of this reaction. CH4 only displays a positive correlation with temperature suggesting a kinetic/thermal control on its forming reaction. The carbon budget of some experiments indicates contamination in agreement with available labeled 13C studies. Salts in initial solutions are possible sources of organic contaminants. Natural systems certainly exploit longer reaction time or other reactional paths to form the observed CH4 and HC. The reducing potential of serpentinization can also produce intermediate metastable carbon phases in liquid or solid as observed in natural samples that should be targeted in future experiments.